TUNING PROCESS OF SINGLE INPUT FUZZY LOGIC CONTROLLER BASED ON LINEAR CONTROL SURFACE APPROXIMATION METHOD FOR DEPTH CONTROL OF UNDERWATER REMOTELY OPERATED VEHICLE - Mohd Aras, Mohd Shahrieel; Jaafar, Hazriq Izzuan; Anuar , Mohamed Kassim (2013)
This study investigates the linear approximation or piecewise linear approximation control surface method for tuning variable parameter of Single Input Fuzzy Logic Controller (SIFLC) for depth control of the underwater Remotely Operated Vehicle (ROV). This method will focus on slope of a linear equation to give optimum performances of depth control without overshoot in system response and faster rise time and settling time. The variable parameter for signed distance method in SIFLC tuning by Particle Swarm Optimization (PSO) algorithm. The optimum parameter will be obtained and approximately no more variable parameter can be tuned because the PSO algorithm will yield optimum parameter. This linear control surface approximation method represents an inference engine of fuzzy logic. The investigation also done based on slope of linear equation either in positive and negative values and come up from conventional FLC that will simplify into SIFLC. The results obtained the slope of linear equation will be affecting the results of system performances.